2020
DOI: 10.1080/10717544.2020.1760403
|View full text |Cite
|
Sign up to set email alerts
|

Chiral 4- O -acylterpineol as transdermal permeation enhancers: insights of the enhancement mechanisms of a transdermal enantioselective delivery system for flurbiprofen

Abstract: In order to devise more effective penetration enhancers, 4-O-acylterpineol derivatives which were expected to be hydrolyzed into nontoxic metabolites by esterase in the living epidermis, were synthesized from 4-terpineol (4-TER) enantiomers and straight chain fatty acids. Their promoting activities on the SR-flurbiprofen and its enantiomers were tested across full-thickness rabbit skin, as well as to correlate under in vitro and in vivo conditions. The permeation studies indicated that both d-4-O-acylterpineol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…4 . The consequents of the IVIVC showed that the in vitro permeation test could be used to forecast the in vivo performance of patches (R 2 >0.8783) [24] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…4 . The consequents of the IVIVC showed that the in vitro permeation test could be used to forecast the in vivo performance of patches (R 2 >0.8783) [24] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…848 The effects of linalool on the enantioselective skin permeation of naproxen has been also explored, 849 as well as the enhancement mechanisms of transdermal enantioselective delivery of flurbiprofen by chiral 4-O-acylterpineol. 850 Very recently, studies focused on the enantioselective permeability of chiral lipid bilayers have been reported. 851 Henriques, Craik, and co-workers showed that the chiral environment of lipid bilayers can modulate the function of membrane-active peptides contrary the view that peptide− lipid interactions are achiral.…”
Section: Enantioselective Adsorption and Permeationmentioning
confidence: 99%
“…l -Menthol has higher permeation-enhancing effects on ( S )-metoprolol than on ( R )- and rac -metoprolol . The effects of linalool on the enantioselective skin permeation of naproxen has been also explored, as well as the enhancement mechanisms of transdermal enantioselective delivery of flurbiprofen by chiral 4-O-acylterpineol . Very recently, studies focused on the enantioselective permeability of chiral lipid bilayers have been reported .…”
Section: Trends In Enantioselective Recognition In Natural and Synthe...mentioning
confidence: 99%
“…This is particularly important for regulating drug penetration by interacting with and modifying the conformation of intercellular proteins. [ 51 , 52 ] So far, many studies have explored the differences in the transdermal penetration of drug enantiomers; however, to date, little attention has been paid to the stereoselectivity effects of chiral supramolecular hydrogels in transdermal delivery and their mechanism of drug penetration. Based on this, it is necessary to study the differences and mechanisms of chiral supramolecular hydrogels in promoting drug penetration in order to better enhance drug transdermal delivery.…”
Section: Introductionmentioning
confidence: 99%